Early Maladaptive Schemas and Core Beliefs in Antisocial Personality Disorder - Turkcapar, Mehmet Hakan; Ozdel, Kadir; Guriz, S. Olga; Hamamci, Zeynep; Duy, Baki; Taymur, Ibrahim; Riskind, John H. (SPRINGER INTERNATIONAL PUBLISHING AG, 2015)
According to cognitive theories of personality disorders, antisocial personality disorder (ASPD) is based upon a distinct set of cognitive-behavioral representations. The aim of this study is to examine this supposition by comparing the early maladaptive schemas (EMSs) and core beliefs of young antisocial men with those of a set of socio-demographically matched, psychiatrically healthy individuals. We used the Schema Questionnaire (SQ-SF) and the Social Comparison Scale (SCS) to identify and evaluate subjects' EMSs and core beliefs. Thirty-eight antisocial individuals and 24 healthy control subjects participated in the study. Results of the SCS indicated that antisocial patients see themselves as unlovable, lonely, and rejected. Results of the SQ-SF indicated that antisocial patients had significantly elevated and clinically relevant scores in comparison to controls in the following areas: emotional deprivation, entitlement/grandiosity, mistrust/abuse, vulnerability to harm and illness, and social isolation. In general, the results of the present study tentatively indicate that while ASPD individuals demonstrate a common profile of core beliefs, these are not unique to individuals diagnosed with ASPD. The implications of these findings are discussed for cognitive behavioral theory, and treatment of ASPD.
Keywords: antisocial; core beliefs; personality disorder; schemas